Perbandingan Proses & Hasil Produksi Radio Visual “Suara Dari Tanah Jauh”: Konvensional vs Versi AI - Ismed, Mohammad (P3M Politeknik Negeri Media Kreatif, 2026)
The integration of Artificial Intelligence (AI) in broadcast media production has brought about significant changes, both in technical aspects and in work structures and creative practices. The visual radio program entitled “Voices from Afar” was chosen as the object of this study because it involves two different approaches: conventional production that relies on human involvement and AI-based production that uses automated systems. This study aims to analyze the differences in the production processes and characteristics of the results of these two models, with an emphasis on work efficiency, technical quality, and aesthetic and narrative dimensions. The method applied is descriptive-comparative qualitative through observation of the production process, in-depth interviews, and content analysis. The results show that AI-based production excels in terms of speed and technical consistency, while conventional production is stronger in narrative depth, emotional expression, and visual authenticity. These findings confirm that AI serves as a creative tool that accelerates the production process; however, AI cannot yet fully replace the human function of creating meaning. Therefore, collaboration between humans and AI is considered an important strategy for the development of visual radio production in the digital media era.